Evaluation of Fluorodeoxyglucose Positron Emission Tomography Scanning in the Neoadjuvant Therapy Paradigm in Pancreatic Ductal Adenocarcinoma. Issue 2 (February 2020) - Itchins, Malinda; Chua, Terence C.; Arena, Jennifer; Jamieson, Nigel B.; Nahm, Christopher B.; O'Connell, Rachel L.; Bailey, Elizabeth A.; Schembri, Geoffrey P.; Gill, Anthony J.; Kneebone, Andrew; Hruby, George; Mittal, Anubhav; et al.
Abstract : Objectives: Little data exist on the utility of fluorodeoxyglucose positron emission tomography (FDG-PET) in operable pancreatic ductal adenocarcinoma (PDAC) treated with neoadjuvant (NA) therapy. Methods: Consecutively treated patients with potentially operable PDAC were recruited from a quaternary referral center between 2015 and 2018. Data were collated on demographic, clinical, radiological, treatment, and disease-free and overall survival (OS) outcome measures, correlated with FDG-PET findings. Results: Of 115 patients recruited, 61% were deemed upfront operable (n = 70), 33% borderline (n = 38), and 6% (n = 7) locally advanced. Ninety-five (83%) received NA chemotherapy with 23 (24%) sequential radiotherapy. Sixty-nine (73%) treated with NA were resected, 37 (54%) attained an R0 resection, 43 (62%) had N1 disease with median tumor viability of 50%. The median OS in the entire cohort was 30.48 months and in those who received NA chemotherapy followed by resection 37.98 months. Twelve percent (n = 13) were upstaged during NA therapy by PET. Preoperative standardized uptake value maximum of less than 5 versus 5 or greater after NA predicted for improved OS, 42.95 months versus 26.05 months, P = 0.02. Conclusions: In this real-world cohort study of PDAC, the utility of FDG-PET in informing the patient treatment pathway was meaningfully demonstrated.